2015
DOI: 10.18632/oncotarget.6802
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid potentiates the anticancer activity of capecitabine in vitro and in vivo in breast cancer models via induction of thymidine phosphorylase expression

Abstract: The prognosis of patients with metastatic breast cancer remains poor, and thus novel therapeutic approaches are needed. Capecitabine, which is commonly used for metastatic breast cancer in different settings, is an inactive prodrug that takes advantage of elevated levels of thymidine phosphorylase (TP), a key enzyme that is required for its conversion to 5-fluororacil, in tumors. We demonstrated that histone deacetylase inhibitors (HDACi), including low anticonvulsant dosage of VPA, induced the dose- and time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…The key step in the process, which is the conversion of 5-deoxy-5-fluorouridine (5-DFUR) to active 5-FU, is catalyzed by TP. 20 Therefore, elevated levels of TP contribute to higher local concentration of the active drugs and increased sensitivity of the cells to chemotherapy of 5-FU. 21,22 Studies have reported that high level of TP expression promotes chemosensitivity and predicts a better outcome in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key step in the process, which is the conversion of 5-deoxy-5-fluorouridine (5-DFUR) to active 5-FU, is catalyzed by TP. 20 Therefore, elevated levels of TP contribute to higher local concentration of the active drugs and increased sensitivity of the cells to chemotherapy of 5-FU. 21,22 Studies have reported that high level of TP expression promotes chemosensitivity and predicts a better outcome in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Studies have reported that high level of TP expression promotes chemosensitivity and predicts a better outcome in different cancer types. 12,20,[22][23][24] Increased level of TP was observed in different pathways, among which activation of NF-kB pathway is one of the main reason for the regulation of TP expression. 11,22 In this study, we observed that PIK3R3 could regulate the transcription level of TP by activation of the NF-kB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC inhibitors including TSA, SAHA and VPA were reported to show synergistic effects by pre-or cotreatment with anticancer drugs. 11,[20][21][22][23][24] The difference in the most significant combination between VPA and TSA/SAHA is not clear, but the differences in the proteome and acetylome profiling between SAHA and VPA might contribute. 25) TSA, SAHA and VPA are all HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the down-regulation of thymidylate synthase overexpression, which occurred in aggressive breast cancer phenotypes, could slow down the disease progression. Consequently, the combined therapy with capecitabine and VPA may result in synergistic action leading to pro-apoptotic and antiproliferative effects in breast cancer cells (21). In addition, pretreatment of breast cancer cells with VPA resulted in their notably increased sensitivity to radiotherapy (3).…”
Section: Breast Cancermentioning
confidence: 99%